A comparative case study: Network agenda setting in crisis and non-crisis news. Issue 3 (September 2016) - Wang, Qian
In order to explore the Chinese traditional media role on social media platforms, this study examined the agenda-setting effects between the networked attribute agendas of Chinese traditional media and various opinion leaders on Weibo in one crisis and non-crisis news, respectively. The results showed that Chinese traditional media failed to lead the discussion on Weibo in both the crisis and non-crisis cases. However, business elites tended to be the most influential opinion leaders in both circumstances. Furthermore, the news agendas of traditional media and the opinion leaders changed in both cases.